Effects of Ni-doping mode on microstructure and mechanical properties of alumina/Ni composites. (15th April 2009) - Jing, Mao-xiang; Shen, Xiang-qian; Li, Wang-xing; Li, Dong-hong
Alumina-based cermets with Ni doping modes of intergranular, intragranular and mixture of both were prepared by hot press-sintering Ni-coated alumina, alumina-coated Ni and co-precipitate powders respectively. The densification process of the cermets from these three Ni/alumina powders was mainly influenced by Ni contents, sintering temperature, and precipitation process of precursor powders. The Ni phase at low contents with small particles located on the interfaces promoted the densification process due to a high reactivity and at high contents to some extent restrained the densification rate while reduced coarsening of alumina grains at high sintering temperatures. The Ni-doping modes could lead to a change in the fracture approach of alumina matrix and improvements of mechanical properties.